Exploring teachers’ perspectives on the use of debates to enhance the speaking skills of lower secondary ESL learners - Christianne Abilekha, Chandra Sekaran (2024)
This study investigates teachers' opinions regarding the effectiveness of debates as an instructional tool for lower secondary English as a second language (ESL) students. This research uses a qualitative methodology to collect data from eight ESL teachers in a variety of schools in order to better understand their perspectives on the advantages and disadvantages of including debates in the curriculum. Semi-structured interviews were used to gather data. The results indicate that debates foster critical thinking, engaged participation, and increased confidence in students; nevertheless, teachers have also identified challenges such disparities in language proficiency and problems with classroom organization. The study concludes with ways for incorporating debates into ESL teaching approaches at the lower secondary level by offering suggestions for best practices and solutions to these problems based on what was shared by the interviewed teachers.